2018
DOI: 10.12688/f1000research.13160.2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of the humoral immune response and viral load of Porcine Circovirus Type 2 in pigs with different vaccination schemes under field conditions

Abstract: Background: Porcine Circovirus type 2 (PCV2) infections are distributed worldwide and cause Porcine Circovirus Associated Disease (PCVAD). To minimize the impact of PCV2 infection on swine health and production, different vaccination schemes have been used since 2006. However, the association between vaccination schemes, virus load and disease under field conditions are not completely understood. Therefore, the objective of this study was to compare the effect of two different PCV2 vaccination schemes on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…From these papers, 10 were excluded based on in-/exclusion criteria. Accordingly, 13 articles [ 4 , 5 , 7 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were finally considered for data collection ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From these papers, 10 were excluded based on in-/exclusion criteria. Accordingly, 13 articles [ 4 , 5 , 7 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were finally considered for data collection ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of period B, we found the absence of PCV2 in reproductive tissues that can be explained by the repeated vaccination of pregnant sows, which agrees with [48], who states that this practice generates protection against reproductive infection. In many countries, including Colombia, it is clear that vaccination against PCV2 has resulted in a decrease in prevalence [49]. In addition, previous studies have shown that regardless of the PCV2 vaccine type, the viral load remained low throughout the production cycle [49].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, including Colombia, it is clear that vaccination against PCV2 has resulted in a decrease in prevalence [49]. In addition, previous studies have shown that regardless of the PCV2 vaccine type, the viral load remained low throughout the production cycle [49].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese hamster ovarian cells K1 (CHO-K1) cells were infected with recombinant lentivirus [3]. PCV2 was propagated in porcine kidney 15 cells (PK15) [5]. Lentivirus vector pCDH-CMV-EF1-Puro, packaging plasmid PLP, PLP1 and PLP2 were preserved by the Microbiology Laboratory of South China Agricultural University (Fitgene Biological Technology Co., Ltd., Guangzhou, China).…”
Section: Cells Lines Plasmids and Virusesmentioning
confidence: 99%
“…Recently, a novel circovirus was identified and tentatively designated as porcine circovirus type 4 (PCV4) [3]. PCV2 infection in pigs causes a series of Porcine circovirus associated diseases (PCVAD), such as postweaning multisystemic wasting syndrome (PMWS), porcine dermatitis nephropathy syndrome (PDNS) and swine reproductive disorder syndrome (SRDS) and other varieties of clinical syndromes, which brings great economic losses to the global pig industry [4,5]. At present, there is no specific drug for PCVAD.…”
Section: Introductionmentioning
confidence: 99%